Investigating the Relationship between Insurance and Economic Growth in GCC Countries - Hamdani, Hanene (Journal of Posthumanism, 2025)
This piece of research seeks to investigate the relationship between insurance and economic growth in the Gulf Cooperation Council (GCC) countries. It aims to explore how different insurance market indicators, such as insurance penetration, insurance premium, and claims ratio, influence the economic growth of these nations. Also, it employs a set of variables to examine the relationship between GDP growth and insurance in GCC countries. The findings show a positive relationship between insurance penetration, insurance premiums and economic growth. However, the claims ratio and inflation rate exhibit mixed effects, indicating the complexity of the relationship between the insurance sector and economic growth. The study enhances our understanding of how insurance markets can promote economic development in GCC countries.